WORK-BASED LEARNING DIGITAL UNTUK MENINGKATKAN KESIAPAN KERJA SISWA PENDIDIKAN VOKASI: SYSTEMATIC REVIEW - Mas’ula Mas’ula; Endah Sudarmilah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Digital transformation requires vocational education to prepare graduates who possess not only technical competencies but also the ability to adapt to technological advances, evolving workplace cultures, and changing industry demands. This study aims to synthesize empirical evidence on the implementation of Digital Work-Based Learning (WBL) and its contribution to improving vocational students' work readiness. The study employed a Systematic Literature Review (SLR) following the PRISMA guidelines. A total of 25 peer-reviewed journal articles with verified DOIs published between 2020 and 2025 were selected based on their relevance to Work-Based Learning, vocational education, digital learning, employability, workplace experience, and career adaptability. Data were analyzed through identification, screening, extraction, and thematic synthesis. The findings indicate that digital WBL is implemented through structured industrial internships, project-based learning, school–industry collaboration platforms, e-learning, mobile learning, gamification, augmented reality, mixed reality, and digital assessment practices that support inclusive learning. These approaches consistently enhance students' technical competencies, soft skills, self-efficacy, reflective ability, career adaptability, and overall work readiness. The effectiveness of digital WBL depends on high-quality industrial supervision, teacher competence, clear task design, continuous feedback, and alignment between vocational curricula and workplace requirements. This review concludes that digital Work-Based Learning is an effective strategy for strengthening vocational graduates' employability while emphasizing the importance of rigorous article selection and source verification to ensure the credibility of systematic review findings. ABSTRAK Transformasi digital menuntut pendidikan vokasi tidak hanya menghasilkan lulusan yang menguasai keterampilan teknis, tetapi juga memiliki kemampuan beradaptasi dengan perkembangan teknologi, budaya kerja, dan kebutuhan industri yang terus berubah. Artikel ini bertujuan menyintesis bukti empiris mengenai penerapan Work-Based Learning (WBL) di era digital serta kontribusinya terhadap peningkatan kesiapan kerja peserta didik pendidikan vokasi. Penelitian menggunakan metode Systematic Literature Review (SLR) dengan mengacu pada pedoman PRISMA. Sebanyak 25 artikel jurnal bereputasi dan memiliki DOI yang diterbitkan pada periode 2020–2025 dipilih berdasarkan kriteria relevansi terhadap Work-Based Learning, pendidikan vokasi, digitalisasi pembelajaran, employability, pengalaman kerja, dan career adaptability. Data dianalisis melalui proses identifikasi, seleksi, ekstraksi, dan sintesis tematik. Hasil kajian menunjukkan bahwa implementasi WBL digital dilakukan melalui magang industri terstruktur, pembelajaran berbasis proyek, platform kolaborasi sekolah–industri, e-learning, mobile learning, gamification, augmented reality, mixed reality, serta asesmen digital yang mendukung pembelajaran inklusif. Penerapan tersebut terbukti berkontribusi terhadap peningkatan keterampilan teknis, soft skills, efikasi diri, kemampuan refleksi, career adaptability, dan kesiapan kerja peserta didik. Efektivitas implementasi WBL digital dipengaruhi oleh kualitas supervisi industri, kompetensi guru, kejelasan tugas, umpan balik yang berkelanjutan, serta keselarasan antara kurikulum dan kebutuhan dunia kerja. Kajian ini menegaskan bahwa WBL berbasis digital merupakan strategi yang efektif untuk memperkuat kesiapan kerja lulusan pendidikan vokasi sekaligus menyoroti pentingnya seleksi dan verifikasi sumber ilmiah dalam menghasilkan sintesis yang kredibel.